Модификация магнитной системы электродвигателя ДВ-3000 с постоянными магнитами - Гребеников, В.В.; Прыймак, М.В.; Шарабан, Ю.В. (Технічна електродинаміка, 2011)
In this paper a numerical investigation of two types of magnetic electric motors is studied. A method for increasing the magnetic induction in the gap of the motor LW-3000 by forming a combined magnetic rotor system based on flat permanent magnets with tangential magnetization and ferromagnetic concentrators of magnetic fluxes is proposed. The influence of the thickness of permanent magnets on the static torque characteristics of the two types of electric motors with identical overall dimensions of stator: radial and tangential magnetization of permanent magnets on the rotor is examined. On the basis of numerical studies have shown that in an electric motor with tangential magnetization of permanent magnets can be 1,7 times larger electromagnetic torque, compared with an electric motor with a radial magnetization of permanent magnets.